2021
DOI: 10.3389/fclim.2021.656479
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Downscaling of Climate Data Using Convolutional and Error-Predicting Neural Networks

Abstract: Numerical weather and climate simulations nowadays produce terabytes of data, and the data volume continues to increase rapidly since an increase in resolution greatly benefits the simulation of weather and climate. In practice, however, data is often available at lower resolution only, for which there are many practical reasons, such as data coarsening to meet memory constraints, limited computational resources, favoring multiple low-resolution ensemble simulations over few high-resolution simulations, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The work by (Serifi, Günther, and Ban, 2021) proposed a method called 'DCN U-Net' which demonstrated a downscaling architecture based on encoder-decoders for highly frequent meteorological data such as precipitation. This approach learns Spatio-temporal functional mapping using U-Net architecture.…”
Section: Methodsmentioning
confidence: 99%
“…The work by (Serifi, Günther, and Ban, 2021) proposed a method called 'DCN U-Net' which demonstrated a downscaling architecture based on encoder-decoders for highly frequent meteorological data such as precipitation. This approach learns Spatio-temporal functional mapping using U-Net architecture.…”
Section: Methodsmentioning
confidence: 99%
“…GeoAI-based downscaling has shown several advantages. For example, CNN is frequently used for downscaling coarse-resolution to fine-resolution precipitation products, using different static and dynamic variables as predictors [82,83]. These studies have shown that CNN achieves different degrees of accuracy, depending on the precipitation rate and the condition complexity; it has, e.g., lower accuracy in extreme wet conditions [83].…”
Section: Hydrological Data Fusion and Geospatial Downscalingmentioning
confidence: 99%
“…However, NWP models still preserve some limitations, the most important being the large number of computational resources needed to generate forecasts. This characteristic limits their outputs' temporal and spatial resolutions (Serifi et al, 2021), shrinking the possibility of offering high detailed forecast. This shortcoming has given place to two scientific tasks in meteorology: providing short-time (between 5 min and 6 hours) forecasts (nowcasting) and generating high-resolution forecasts from low-resolution (downscaling).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of precipitation Sha et al (2020) developed a U-Net-based model to downscale daily precipitation forecasts from a low to a higher resolution, obtaining results that overcome the performance of the statistical downscaling methods. One year later, Serifi et al (2021) used generative models to downscale temperature and precipitation maps from weather simulations and meteorological observations, obtaining improved-quality high-resolution maps while avoiding blurred results typical of the deconvolution.…”
Section: Introductionmentioning
confidence: 99%